Dementia friendly communities in Kingston upon Thames - Collaboration with partner organisations - Tatai, Tamas (Magyar Gerontológia, 2024)
Alzheimer’s Society is the largest UK charity focusing on dementia and the only one to tackle every aspect of dementia. Currently 900,000 people are living with dementia in the UK. In the country it is estimated that 39% of people with dementia live in care settings, whereas 61% live in the community. This data highlights the importance and necessity of transforming our local communities and making them dementia friendly.